1994
DOI: 10.1042/cs0860317
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Insulin Sensitivity in Man: A Comparison of Minimal Model- and Euglycaemic Clamp-Derived Measures in Health and Heart Failure

Abstract: 1. Simplified protocols for the measurement of insulin resistance will facilitate studies of this potentially important variable. 2. Using the euglycaemic clamp as the reference technique, we have assessed the validity of the insulin sensitivity index (inversely related to insulin resistance) obtained using a high-dose (500 mg/kg), unmodified intravenous glucose tolerance test with a 16 point sampling schedule and analysis using the minimal model of glucose disappearance. The two methods were compared in 10 cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(23 citation statements)
references
References 0 publications
2
21
0
Order By: Relevance
“…However, it is of some concern that the two methods are apparently not measuring the same metabolic parameter, since the intercept of the plot, Figure 2, is clearly not equal to zero. This parallels closely the situation for the IVGTT itself, which has been compared with clamps on a number of occasions [3, 7, 2831]. A significant relationship between the IVGTT and clamp was not achieved in an early study with a very homogenous population [29], but was later demonstrated when wider spectrums of insulin sensitivity were investigated [3, 7].…”
Section: Discussionsupporting
confidence: 52%
“…However, it is of some concern that the two methods are apparently not measuring the same metabolic parameter, since the intercept of the plot, Figure 2, is clearly not equal to zero. This parallels closely the situation for the IVGTT itself, which has been compared with clamps on a number of occasions [3, 7, 2831]. A significant relationship between the IVGTT and clamp was not achieved in an early study with a very homogenous population [29], but was later demonstrated when wider spectrums of insulin sensitivity were investigated [3, 7].…”
Section: Discussionsupporting
confidence: 52%
“…Both impaired skeletal muscle glucose uptake and impaired insulin‐mediated inhibition of endogenous glucose production has been demonstrated using the glucose clamp technique [23]. This has been confirmed in larger studies using a minimal model approach and an intravenous glucose tolerance test [24, 25]. The molecular mechanisms underlying skeletal muscle insulin resistance are not fully understood [7, 26, 27].…”
Section: Discussionmentioning
confidence: 99%
“…This sample comprised five groups of 20 IVGTTs from studies of apparently healthy pre-and post-menopausal women (groups 1 and 2) [16,17], apparently healthy men (group 3), and men with coronary heart disease (group 4) or chronic heart failure (group 5) [18]. Insulin sensitivity estimates derived using this protocol have been shown to correlate well with those from the euglycaemic hyperinsulinaemic clamp, and to behave as expected in situations in which variation in insulin sensitivity has been previously well characterized [8,19]. The first 20 consecutive IVGTTs by date-of-test in each group were selected for inclusion in the present analysis.…”
Section: Ivgtt Datamentioning
confidence: 72%
“…In a previously published study [8], 15 volunteers (10 apparently healthy men and women and five patients with chronic heart failure) each underwent a euglycaemic hyperinsulinaemic clamp and an IVGTT according to the protocol described above. In the present study, the IVGTT data were re-analysed according to the four most successful implementation procedures, and the values for S I obtained were correlated with a clamp-derived measure of insulin sensitivity.…”
Section: Comparison With the Euglycaemic Clampmentioning
confidence: 99%